Graphene for biomedical applications:a review - Azrul Azlan Hamzah,; Reena Sri Selvarajan,; Burhanuddin Yeop Majlis, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Since its discovery in 2004, graphene has enticed engineers and researchers from various fields to explore its possibilities to be incepted into various devices and applications. Graphene is deemed a ‘super’ material by researchers due to its extraordinary strength, extremely high surface-to-mass ratio and superconducting properties. Nonetheless, graphene has yet to find plausible footing as an electronics material. In biomedical field, graphene has proved useful in tissue engineering, drug delivery, cancer teraphy, as a component in power unit for biomedical implants and devices and as a vital component in biosensors. Graphene is used as scaffolding for tissue regeneration in stem cell tissue engineering, as active electrodes in supercapacitor for powering wearable and implantable biomedical devices and as detectors in biosensors. In tissue engineering, the extreme strength of monolayer graphene enables it to hold stem cell tissues as scaffold during in-vitro cell regeneration process. In MEMS supercapacitor, graphene’s extremely high surface-to-mass ratio enables it to be used as electrodes in order to increase the power unit’s energy and power densities. A small yet having high energy and power densities cell is needed to power often space constrainted biomedical devices. In FET biosensors, graphene acts as detector electrodes, owing to its superconductivity property. Graphene detector electrodes is capable of detecting target molecules at a concentration level as low as 1 pM, making it the most sensitive biosensor available today. Graphene continues to envisage unique and exciting applications for biomedical field, prompting continuous research which results and implementation could benefit the general public in decades to come.